Full Thickness Retinal Hole Formation after Nd:YAG Laser Hyaloidotomy in a Case with Valsalva Retinopathy - Yasin Sakir Goker; Kemal Tekin; Cemile Ucgul Atilgan; Pinar Kosekahya; Pelin Yilmazbas (Case Reports in Ophthalmological Medicine)
A 27-year-old male was presented with a sudden onset of visual loss in his right eye. A secondary care center referred the patient with fundus photographs which were screened 4 days before and after the Nd: YAG laser hyaloidotomy treatment. Snellen acuity was 10/10 in both eyes. Fundus examinations revealed a retinal pigment epithelium (RPE) alteration at the margin of the inferior temporal arterial vascular arcade in the right eye and resolved preretinal and subretinal hemorrhages were seen in the macula. A diagnosis of Valsalva retinopathy was made based on the history and the treatment photographs of Nd:YAG laser hyaloidotomy. At 1st month examination all hemorrhages were resolved but RPE alterations were still at the margin of the inferior temporal arterial vascular arcade. The optical coherence tomography angiography (OCTA) images revealed 2 lesions. On en face OCT angiogram of OCTA full thickness retinal hole formation and ellipsoid zone damage at the superior and inferior margin of the inferior temporal arterial vascular arcade were seen. Superficial vascular plexus was also damaged at that region. The projection of the evacuation of blood from subhyaloid space and the full thickness retinal hole formation were the same, indicating that the partial and full thickness retinal holes were created by the laser treatment.